2016
DOI: 10.3390/su8040392
|View full text |Cite
|
Sign up to set email alerts
|

A Two-Step Strategy for Developing Cultivated Pastures in China that Offer the Advantages of Ecosystem Services

Abstract: Based on a site experiment on a typical steppe of Inner Mongolia, the short term effects on aboveground biomass, soil water content, soil organic carbon, and soil total nitrogen of four cultivated pastures (CPs) with different compositions of herbaceous species were examined and compared to those of adjacent, natural grassland (NG) enclosed simultaneously. All CPs produced significantly higher aboveground biomass than did the NG after two years of establishment, and the mixed culture of Agropyron cristatum (A.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Its grassland covers an area of 78 million ha and accounts for 21.7% of China's total grassland area, supporting this ethnic region as the largest of the country's five major pastoral regions [12]. However, due to rapid population growth, intensive and improper anthropogenic activities (mainly grazing and reclamation), and adverse effects of droughts exacerbated by climate change [13][14][15][16], approximately 90% of Inner Mongolia's natural grassland has been degraded to some extent [17,18]. Acknowledged as an important ecological barrier for northern China, grassland degradation of this magnitude can cause several regional or even global environmental problems [19,20], of which the most prominent is the frequent occurrence of severe sandstorms and dust storms sweeping across northern China in recent decades, especially around Beijing and adjacent regions.…”
Section: Introductionmentioning
confidence: 99%
“…Its grassland covers an area of 78 million ha and accounts for 21.7% of China's total grassland area, supporting this ethnic region as the largest of the country's five major pastoral regions [12]. However, due to rapid population growth, intensive and improper anthropogenic activities (mainly grazing and reclamation), and adverse effects of droughts exacerbated by climate change [13][14][15][16], approximately 90% of Inner Mongolia's natural grassland has been degraded to some extent [17,18]. Acknowledged as an important ecological barrier for northern China, grassland degradation of this magnitude can cause several regional or even global environmental problems [19,20], of which the most prominent is the frequent occurrence of severe sandstorms and dust storms sweeping across northern China in recent decades, especially around Beijing and adjacent regions.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, increased forage production could make up the insufficiency of available forage in the desert regions of the MBS in the winter. This low-input forage cropping system provides beneficial ecosystems services, at least in the short term, and it could be the first step of cultivated pasture development strategy for China based on current social-economic conditions [51].…”
Section: Species Interactionsmentioning
confidence: 99%
“…Although fertilizer‐use efficiency has been shown to be very low in the ecosystems, because of the low nutrient holding capacity of the soils (Zeng et al, ), legume species have been found to potentially increase N availability and community productivity in sandy grasslands (Herben et al, ; Spehn et al, ) to a greater extent than the use of fertilizers (Torabian, Farhangi, & Denton, ). Although both ecological and economic benefits have been demonstrated, the area of sandy grasslands planted with legumes remains very small in China relative to Europe and New Zealand (Chen et al, ). Furthermore, to our knowledge, no study has examined the combined effects of sediment addition and legume cultivation on sandy grassland productivity.…”
Section: Introductionmentioning
confidence: 99%
“…To control degradation and protect the regional environment, some measures (e.g., planting indigenous trees and shrubs, planted grasslands, and natural recovery) to recover ecosystem function have been implemented in China in recent decades (Li et al, 2018;Su, Li, Cui, & Zhao, 2005;Wu, Liu, Zhang, Hu, & Chen, 2010). Of particular relevance for sandy grasslands, cultivation of previously arable land with perennial grasses and legumes is now being adopted (Chen, He, Tang, Zhao, & Shao, 2016). Legume cultivation may be particularly beneficial because the productivity of sandy grasslands in China is considered to be mainly limited by nitrogen (N).…”
mentioning
confidence: 99%